2022
DOI: 10.26441/rc21.1-2022-a22
|View full text |Cite
|
Sign up to set email alerts
|

De consumidores a prosumidores: la narrativa transmedia en dos juegos móviles para adolescentes y jóvenes

Abstract: En las últimas décadas, los juegos digitales se han convertido en parte esencial de la cultura de los adolescentes y jóvenes. Los consumidores de contenidos de estas plataformas se han incrementado notablemente, así como los estudios en torno a ellos. El objetivo de esta investigación consiste en analizar los contenidos generados por los usuarios en los juegos móviles Episode: Choose Your Story y Choices: Stories You Play, los cuales poseen una gran cantidad de usuarios jóvenes que difunden y expanden las hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Several authors, such as Yucra et al (2022), Karbaum (2018), Mateus et al (2022), Fernández et al (2020), and Martinez et al (2018, had the same topic of interest, prosumers and their contents, thus being Peru and Spain where projects of great relevance were shared. Thanks to a collaboration between authors from both countries, it was possible to research the users of 2 mobile games that are characterized by having a greater number of followers, through an exploratory character based on narrative and content analysis, it was shown that the relevance of video games promote users to not only consume them but they are also influenced to be the creators of their content, thus developing the creativity of the player (Yucra et al, 2022), because, it is the prosumer of today, the existence of artifacts facilitates the creation of content, using different narratives that are part of the new communicational environment (Karbaum, 2018) and it is the prosumers who participate in user-user and some user-brand interaction channels to increase the gratifications desired by the organizations (Martinez et al, 2018).…”
Section: Prosumers and Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors, such as Yucra et al (2022), Karbaum (2018), Mateus et al (2022), Fernández et al (2020), and Martinez et al (2018, had the same topic of interest, prosumers and their contents, thus being Peru and Spain where projects of great relevance were shared. Thanks to a collaboration between authors from both countries, it was possible to research the users of 2 mobile games that are characterized by having a greater number of followers, through an exploratory character based on narrative and content analysis, it was shown that the relevance of video games promote users to not only consume them but they are also influenced to be the creators of their content, thus developing the creativity of the player (Yucra et al, 2022), because, it is the prosumer of today, the existence of artifacts facilitates the creation of content, using different narratives that are part of the new communicational environment (Karbaum, 2018) and it is the prosumers who participate in user-user and some user-brand interaction channels to increase the gratifications desired by the organizations (Martinez et al, 2018).…”
Section: Prosumers and Contentmentioning
confidence: 99%
“…Along these lines, other publications have focused on prosumers, who are users who were originally consumers of content and have leaped to be the ones who now produce content for others while consuming content from third parties. For example, in Peru and Spain, through a collaboration, the content generated by prosumer users of mobile games, who disseminate content through social media storytelling on digital platforms, was investigated and analyzed (Yucra et al, 2022). In Spain and Italy, an analysis of the interrelationship of a digital music platform with consumer and prosumer users was sought (Vizcaíno et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Las humanidades están en declive (Whalley, 1985;Reiter, 2017;Nussbaum, 2010) y tal propensión al abandono de esta rama del saber se refleja en la producción investigativa de los estudiantes de Literatura en una universidad del sur peruano. La cantidad de trabajos de investigación publicadas es escasa con relación al número de egresados de la Escuela Profesional de Literatura y Lingüística, que representan un total de 153 egresados entre el 2017 y 2021.…”
Section: Discusión Y Conclusionesunclassified
“…n el texto Studies in Literature and the Humanities: Innocence of Intent, George Whalley (1985) enunciaba que las humanidades eran vistas con menor estima a los ojos del público y de las autoridades, como si fueran obsoletas o sin relevancia para las necesidades modernas y advierte sobre una ola de abandono de las humanidades. Esta inclinación se refleja en la predilección de las ciencias, las matemáticas y la tecnología (Reiter, 2017), por sobre las disciplinas humanísticas.…”
Section: Introductionunclassified